2020
DOI: 10.1101/2020.08.20.20178608
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of an urban sanitation intervention on childhood enteric infection and diarrhea in Maputo, Mozambique: a controlled before-and-after trial

Abstract: Background. Onsite sanitation serves more than 740 million people in urban areas, primarily in low-income countries. Although this critical infrastructure may play an important role in controlling enteric infections in high-burden settings, its health impacts have never been evaluated in a controlled trial. Methods. We conducted a controlled before and after trial to evaluate the impact an onsite urban sanitation intervention on the prevalence of bacterial and protozoan infection (primary outcome), soil trans… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
19

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 84 publications
(142 reference statements)
0
29
0
19
Order By: Relevance
“…When comprehensive interventions are not possible, efforts targeting either source or contact control are necessary to progress toward the drastic reduction in dose, which our model indicates is needed to achieve acceptable levels of risk. Although rigorous trials of sanitation infrastructure found that effective source control may be a distant prospect in LMICs, 7 12 , 42 contact control, while insufficient, may be important in the near-term to reduce infection risks.…”
Section: Discussionmentioning
confidence: 99%
“…When comprehensive interventions are not possible, efforts targeting either source or contact control are necessary to progress toward the drastic reduction in dose, which our model indicates is needed to achieve acceptable levels of risk. Although rigorous trials of sanitation infrastructure found that effective source control may be a distant prospect in LMICs, 7 12 , 42 contact control, while insufficient, may be important in the near-term to reduce infection risks.…”
Section: Discussionmentioning
confidence: 99%
“…This study was linked to the Maputo Sanitation trial (MapSan), which evaluated an urban shared sanitation intervention ( clinicaltrials.gov registration: NCT02362932) ( Knee et al, 2020 ). We used the trial as a vehicle, but our study is not an evaluation of the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The intervention impact on fecal contamination was evaluated using a controlled before-and-after (CBA) study design. 5,43 Children in each intervention compound were enrolled immediately before the new latrine was opened for use, with concurrent enrollment of control compounds conducted at a similar frequency. Follow-up visits to each compound were conducted approximately 12 months following baseline enrollment.…”
Section: Methodsmentioning
confidence: 99%
“…2–4 Recent evaluations of a range of WASH interventions found inconsistent and largely negligible impacts on child diarrhea, growth, and enteric infection. 512 Notably, combined interventions did not provide greater protection than their constituent interventions alone, suggesting that key sources of pathogens and pathways of exposure are inadequately addressed by conventional WASH strategies. 6,7,9,1315…”
Section: Introductionmentioning
confidence: 99%